An exploration of the structure of mentors' behavior in nursing education using exploratory factor analysis and Mokken scale analysis. (May 2016) - Chen, Yanhua; Watson, Roger; Hilton, Andrea
Abstract: Background: To understand nursing students' expectation from their mentors and assess mentors' performance, a scale of mentors' behavior was developed based on literature review and focus group in China. Objectives: This study aims to explore the structure of mentors' behavior. Design: A cross-sectional survey. Setting: Data were collected from nursing students in three hospitals in southwest China in 2014. Participant: A total of 669 pre-registered nursing students in their final year clinical learning participated in this study. Methods: Exploratory factor analysis and Mokken scale analysis was employed to explore the structure and hierarchical property of mentors' behavior. Results: Three dimensions (professional development, facilitating learning and psychosocial support) were identified by factor analysis and confirmed by Mokken scaling analysis. The three sub-scales showed internal consistency reliability from 87% to 91%, and moderate to strong precision in ordering students' expectation about mentors' behavior and a small Mokken scale showing hierarchy was identified. Conclusion: Some insight into the structure of mentoring in nursing education has been obtained and a scale which could be used in the study of mentoring and in the preparation of mentors has been developed. Highlights: Mentors' behavior is conceptualized as an three-dimensional structure: psychosocial support, facilitating learning and professional development. Mentorship is hierarchical; some behaviours are perceived as more important than others. This tool can be useful to guide mentors' behaviour and enhance the communication between students and mentors in China Policy implication: mentors' training program should contain the three factors; treat students as learner and respect them should be emphasized.